Revisiting the Intracranial Neurological Imaging Manifestations of Human Immunodeficiency Virus: Pictorial Review with a Pattern-Based Approach - Mehra, Shibani; Verma, Deepak; Bansal, Lukshay (Indian Journal of Radiology and Imaging, 2025)
Human immunodeficiency virus (HIV) leads to a spectrum of pathologies from head to toe. This review focuses on the neurological complications associated with HIV infection. It highlights both direct effects, resulting from virus' direct impact on central nervous system (CNS), and indirect effects, stemming from progressive decline in CD4 counts. Direct effect encompasses HIV-associated neurocognitive disorder (HAND) and HIV-associated vasculopathy. Indirect effect comprises all the opportunistic infections that an individual is predisposed too, including toxoplasmosis, cryptococcal meningitis, and progressive multifocal leukoencephalopathy. Radiological imaging plays a crucial role in diagnosis and distinguishing of all these entities, which can have overlapped clinical presentation. The imaging characteristics are distinctive, such as, HAND presents with symmetrical bilateral white matter hyperintensities on magnetic resonance imaging, while cerebral toxoplasmosis typically shows a target sign with multiple ring enhancement, and cryptococcal meningitis has a typical “soap bubble appearance.” Meanwhile, progressive multifocal leukoencephalopathy is identified by asymmetric T2 hyperintensities without enhancement. This review also covers CNS-immune reconstitution inflammatory syndrome, a critical condition linked with antiretroviral therapy. This broad spectrum of presentation underscores the need for a systematic, pattern-based approach to enhance diagnostic accuracy, which is provided at the end.
Keywords: HIV; MRI; toxoplasmosis; PML; encephalopathy; lymphoma; cryptococcoma